RETRACTED: Effect Of Age, Gender, And Tax Rates On Tax Compliance (Case Study At Kpp Pratama Jakarta Tanah Abang Dua) - Putri Nurjanah Irnanda; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
The purpose of this study was to determine the effect of age, gender, and tax rates on tax compliance with income level as a moderating variable at KPP Pratama Jakarta Tanah Abang Dua. This study uses a quantitative approach with an emphasis on testing theory by measuring numbers and conducting data analysis. The measurement model or outer model used in this study is the convergent validity test, discriminant validity test, and reliability test. Tax compliance has a major impact on state revenues. This situation is in accordance with the compliance level data obtained from the Jakarta Tanah Abang Dua KPP Pratama, namely during 2017 to 2021 where the realization of Tax Compliance is still unstable from the Tax Compliance target. The results of this study indicate that Age and Tax Rates have a significant effect on Tax Compliance and Income Levels can moderate significantly, so the older a person is and one's belief in the currently set tax rate, the higher the level of Tax Compliance. While gender has a negative effect on tax compliance and income levels cannot be significantly moderated, the increase in tax compliance is not based on a person's gender.